O pewnych zasadach sztuki publicystycznej w prasie opiniotwórczej: temporalność i argumentacyjność - Kula, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
The rules of opinion journalism, presented in numerous source materials, indicate that an opinion article is constructed in line with the argumentative order: the right selection of arguments is to result in proving a thesis put forward in the text. However, more and more frequently opinion journalists offer the readers an attempt at finding out about the meanderings of politics or the economy single-handedly: temporal narration ordering fragments of texts allows to trace events “frame by frame”. Short sentences, nominal statements, verbs impersonal forms, in the present tense: the reader has no problem with following them. The reader learns about the answers to basic questions important in construing journalism information. Creation of some sort of a report is a transformation stage in an opinion journalist’s work; to a reader this is an extra and superfluous element. The phenomenon of temporality is also related to the fact that the analysed texts are about themselves: by resorting to the first person singular/plural, the author or authors describe their journalist activities, meetings with specific individuals (sources of information), problems with data verification, sometimes with obtaining data. In the course of analyses, the following relation emerges: redundancy – condensation necessitating a more in-depth analysis with respect to the rules underlying contemporary opinion journalism genres.